OP0249-PARE 25 Years of Camp Freedom - A 6 Day Camp for Children 7-17 Years Old with Arthritis. (15th July 2016) - Mace, K.
Abstract : Background: Camp Freedom was developed by the Arthritis Foundation of Western Australia in conjunction with Princess Margret Hospital for Children in 1990 for children with arthritis, with a camp manual having been produced as a guide into the preparation and development of each camp. Objectives: The aim of Camp Freedom is to empower young people with all forms of Arthritis to make informed choices with regards to lifestyle, education and disease management. The camp is designed to offer friendship, fun and exciting activities as well as educational workshops. This also provides respite for the family. Methods: Preparation for camp begins with the selection of the campsite, forming an enthusiastic team is our next step, our team consists of a Camp Coordinator and our volunteers are a Pediatric Rheumatology Nurse Specialist, a Pediatric Rheumatologist and 7–10 Peer leaders over the age of 21, most having been previous campers. A programme is created to keep the children occupied most of the time during the 6 day camp, with confidence building a prime outcome to most of our activities, with abseiling, flying fox, sports and fun actvities planned. Our education sessions are undertaken in two sections, for our junior and senior campers, the subjects and methods are very different, with our health professionals providing age appropriate information and subject matter. Junior camper topics are generally related to understanding the mechanics of their joints, how Arthritis affects them and how to handle bullying. Whereas with the senior campers more detailed interactive subjects such as Transition, peer pressure and social issues are discussed, generally in two sessions, the first with peer leaders and the second with our Health professionals in attendance to answer the questions from the previous session. Results: At the end of each camp we ask the participants to fill in a feedback form to make sure we are providing them with activities and information they need and to give us information to change and improve our programme. We think the biggest accolade is that the parents allow their children to attend camp year after year, if they didn't think they benefited from camp they wouldn't allow them to attend. Seeing the change that has happened to many of the campers, arriving as shy, negative, closed children who hate their difference to their other friends, at the end of camp to be kids who are vibrant outgoing young people who have made lifelong friends all because they just "get each other". They don't have to explain why they take medications, or why they have a limp today but not yesterday, or why they have to sit down for a while after exercise, they are all in the same boat, although at different levels. Camp gives the kids the chance to discuss their condition with someone just like them, to know they aren't alone and can share their experiences, without having to explain themselves. Conclusions: Many of our outcomes are not measurable on a piece of paper but having been involved with Camp Freedom for 18 years seeing the campers grow up and now returning as adult peer leaders is a very rewarding outcome. Camp Freedom is very successful and growing due to the caring and nurturing nature of the week. The kids are allowed to be kids; they don't have well meaning but overprotective parents around to stop them from "having a go". Disclosure of Interest: None declared